Mr. Sunny is funny! - Gutman, Dan; Paillot, Jim (New York, NY Scholastic Inc., 2015)
A.J.'s summer vacation is ruined when yucky Andrea's family rents the beach house next door. Her crush on the lifeguard, Mr. Sunny, is driving everyone crazy.
Originally published in 2008 by HarperCollins Children's Books.
Ages 7-10.
Accelerated Reader/Renaissance Learning
110802
Keywords: Vacations -- Juvenile fiction; Summer -- Juvenile fiction; Beaches; Humorous stories; Humorous fiction; Juvenile works